Effects of Early or Conventional Weaning on Beef Cow and Calf Performance in Pasture and Drylot Environments - G. W. Preedy; J. R. Jaeger; J. W. Waggoner; K C Olson; K. R. Harmoney (Kansas Agricultural Experiment Station Research Reports, 2018)
During widespread drought, pasture availability and productivity are reduced. This, coupled with increasing land prices and lease rates, has prompted the evaluation of alternative management strategies that decrease grazing pressure on perennial pasture or reduce feed and pasture costs. Weaning early and moving cows from pasture to a drylot environment is used commonly for reducing grazing pressure on perennial pastures. A premature end to lactation reduces cow nutrient requirements and reduces grazing pressure. Removal of the calf further reduces grazing pressure, as calves are significant consumers of forage dry matter (DM) during mid and late lactation. The combination can be used to extend grazing by 0.4 d for each d weaning is executed earlier than normal. Early weaning may result in calves having less value at weaning compared to calves weaned at conventional ages. Retaining ownership of young calves through backgrounding can be useful for increasing their value. Limit-feeding non-lactating cows or cow-calf pairs in confinement can also reduce grazing pressure on pastures, while maintaining cow body condition score (BCS) or body weight (BW). Previous research conducted at the location of this study found that limit-feeding non-lactating cows at 1.9% BW achieved acceptable gains in BW, BCS, and rump fat. Therefore, the objective of our study was to evaluate the performance of beef cows and calves subject to a 56-d early or conventional weaning period in either pasture or drylot environments.
Keywords: beef cows; concentrate; early weaning; pasture